An integrated approach using social support theory and technology acceptance model to investigate the sustainable use of digital learning technologies - Sultan Hammad Alshammari; Abeer F. Alkhwaldi (Scientific Reports)
Abstract The present study explored the determinants influencing students’ intentions towards utilizing digital learning technologies (DLTs). It proposes a holistic view model for students’ utilization of digital learning technologies by integrating social support theory and the “Technology Acceptance Model” (TAM). Data were gathered from 262 students of the University of Ha’il through utilizing a questionnaire. Two steps in SEM were applied for data analysis: CFA was employed to develop the model measurement, and SEM was conducted to analyze the relationships between constructs. The results revealed that “Educational Support” (EDS) significantly affected students’ “behavior intention” (BI) to utilize digital learning technologies through perceived usefulness (PU) (EDS→PU: β = 0.338, p < 0.05). Furthermore, “Emotional support” (EMS) significantly affected behavioral intention through both “perceived ease of use” (PEU) and PU (EMS→PEU: β = 0.635, p < 0.05; EMS→PU: β = 0.310, p < 0.05). Surprisingly, students’ “perceived ease of use” (PEU) did not affect digital learning technologies’ “perceived usefulness” (PU) (PEU→PU: β = 0.195, p > 0.05). The present study contributes to a refined understanding of how educational and emotional support influence students’ receptivity towards and engagement with learning technologies. Thus, institutions and universities should enhance their students’ educational and emotional support to facilitate the successful utilization of digital learning technologies. Furthermore, the study revealed that PU and PEU affected students’ intentions to utilize DLTs. Thus, PU and PEU can enhance the utilization of digital learning technologies. This study provides practical implications that educational institutions and universities could apply to achieve successful usage of these digital learning technologies.